Positional Concerns among the Poor: Does Reference Group Matter? Evidence from Survey Experiments. (14th July 2014) - Akay, Alpaslan; Andersson, Lisa; Martinsson, Peter; Medhin, Haileselassie
Abstract : Previous research studies suggest a lower degree of positional concerns among people from poor countries. Yet the evidence is limited and most often builds on the assumption that people's reference groups are the same across all individuals. We conduct a survey experiment in urban Ethiopia that is modified to include multiplicity of reference groups. We estimate positional concerns considering various reference groups to test whether the low positional concerns found in the literature are due to misspecification of the reference groups. The results show a low degree of positional concern, which is highly stable across different reference groups.